Dampak Literasi Keuangan, Overconfidence, dan Availability Bias terhadap Keputusan Investasi: Peran Moderasi Persepsi Risiko - Naila Syakirotul Rizqiyah; Fakhmi Zakaria; Vicky Oktavia; Almira Santi Samasta (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This research examines the factors that shape investment decision-making in the capital markets within Generation Z members of investment communities in Central Java, focusing on the variables of financial literacy, overconfidence, and availability bias, as well as risk perception as a moderating variable. This present research utilized a quantitative design, collecting primary data from respondents through an online questionnaire. The analysis method applied is SEM-PLS with aid of SmartPLS software version 4, encompassing the outer and inner models. The findings reveal that financial literacy and overconfidence have a positive significance influence on investment decisions, while availability bias does not show any significant influence. Furthermore, the interaction of risk perception in moderating the relationship between overconfidence and investment decisions was found to be significantly negative, whereas the interaction of risk perception on the relationship between availability bias and investment decisions demonstrates a positive significant effect.